Tenacious D in the Pick of Destiny [videorecording (DVD)] - Lynch, Liam; Black, Jack, 1969-; Gass, Kyle; Gentile, Troy; Tompkins, Paul F.; Grohl, David (New Line Home Entertainment : Distributed by Warner Home Video, 2007)
Witness the birth of Tenacious D, the self-proclaimed greatest rock band of all time. On a fateful day on Venice beach, JB and KG meet and realize that they were destined to make history by combining their musical genius. But when overnight success eludes them, they set out to find the legendary "Pick of Destiny"--A special guitar pick believed to possess magical powers that can turn any open-mike wannabe into a rock legend.